Penerapan Model Pembelajaran Kooperatif Tipe Make A Match Berbantuan Pakapin untuk Meningkatkan Pemahaman Konsep Geometri Peserta Didik Kelas 2 Sekolah Dasar - Afif, Muhammad Miftahudin; Purbasari, Imaniar; Kamal, Jamaluddin (Yayasan Pendidikan Insan Mulia Utan Sumbawa, 2025)
This research aims to improve the conceptual understanding of geometry among second-grade elementary school students through the implementation of the cooperative learning model Make A Match supported by the Papan Kantong Pintar (PaKaPin) instructional media. The background of this research is based on students' low comprehension of geometric concepts, particularly in the topics of plane and solid figures. Students encountered difficulties in identifying characteristics of various geometric shapes and distinguishing elements such as vertices, sides, and edges, which was also influenced by the lack of concrete learning media. The study employed a Classroom Action Research (CAR) method using the spiral model developed by Kemmis and McTaggart, conducted in two cycles. Data were collected through learning outcome tests and analyzed using both quantitative and qualitative approaches. The results showed a significant improvement in students' understanding of geometry, with learning mastery increasing from 13% (pre-cycle) to 52% in cycle I, and reaching 87% in cycle II. The average score also rose from 60.43 to 79.39, and then to 86.48. The implementation of the Make A Match model and PaKaPin media proved effective in enhancing students’ conceptual understanding of geometry while fostering an active, interactive, and enjoyable learning environment. Therefore, this method combination can serve as an innovative solution for mathematics instruction at the elementary school.